Assessment of Calcium Carbonate Coating on Osseointegration of Commercially Pure Titanium Implant by Torque Removal Test and Histomorphometric Analysis - Mahmood, Mustafa S.; Al-Ameer, Shatha S. (Journal of Baghdad College of Dentistry, 2017)
AbstractBackground: One of the most important methods to replace lost teeth is dental implants. In order to increase the strength of connection of the implant with the jaw bone to provide early loading after placement, implant is coated by different coating materials that achieved that purpose. The aim of this study was to evaluate the influence of coating CP Ti implant with calcium carbonate on the strength of bone-implant interface after two and six weeks of implantation in rabbit femur bone by torque removal test, histological and histomorphometric analysis.Materials and methods: Coating the surface of commercially pure titanium screws with extra pure synthetic calcium carbonate via electrophoretic deposition method (EPD) was done. The surface of disc samples after coating was checked by optical microscopy, X-ray diffraction examination and measurement of coating thickness. Ten male white French rabbits were prepared for implantation. Forty screws were implanted in the femur bone, two implant screws in each femur bone. The first screw is coated with calcium carbonate and compared with the second uncoated screw. Rabbits are divided into two groups according to the healing periods 2 and 6 weeks. By torque removal, the osseointegration is measured. Single screw from each group was used for histological and Histomorphometric analysis.Results: There was significant increased mean torque removal for screws coated with calcium carbonate compared with uncoated screws. Histological examination showed an increase in the growth of bone cells for coated screws, and the histomorphometric analysis showed an increase in new bone formation percent (NBFP).Conclusion: Coating the surface of the CP Ti implant with calcium carbonate via electrophoretic deposition method had great effect in increasing the osseointegration than uncoated surface.